Identification of a gene that positively regulates expression of listeriolysin, the major virulence factor of listeria monocytogenes. - Leimeister-Wächter, M (1990)
We have isolated, by molecular cloning and genetic complementation of a listeriolysin-negative mutant, a gene required for the expression of this virulence factor in Listeria monocytogenes. The mutant strain SLCC53, which was nonhemolytic and avirulent, harbored a deletion of 450 base pairs located approximately 1500 base pairs upstream of the listeriolysin gene. No transcripts corresponding to the listeriolysin gene were detected in the mutant. DNA sequencing of this region from the hemolytic strain EGD revealed that the region deleted in the mutant would abrogate expression of a 27-kDa polypeptide. Introduction of a recombinant plasmid expressing this 27-kDa polypeptide restored hemolytic activity to the mutant and increased the hemolytic activity of the wild-type L. monocytogenes strain EGD. We have designated the gene encoding the 27-kDa polypeptide prfA, for positive regulatory factor of listeriolysin (lisA) expression. The prfA gene regulates transcription of the lisA gene positively.